Physicochemical properties, antioxidant activities, and sensory evaluation of pineapple peel biovinegar - Yashini K., Selvanathan; N., Masngut (IOP Publishing, 2020)
The objective of this study was to characterize a biovinegar (OPPB) produced from natural fermentation of pineapple peel. Physicochemical properties, antioxidant activities and sensory evaluation were investigated to compare its quality with apple cider vinegar (ACV) and dates vinegar (DV). The vinegars were evaluated for their scavenging activity towards 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical for the antioxidant activities. Physicochemical properties such as ascorbic acid, reducing sugar, acidity, acetic acid, ethanol, total soluble solid, pH and sucrose content were also determined. Consumer preferences and perception towards the biovinegar were carried out through a survey. The OPPB shows a comparable radical scavenging of 82 % and physicochemical properties such as acidity of 3.03 %, ascorbic acid of 1.43 mg equi. AA/100 mL sample, pH of 3.16, acetic acid of 0.61 %, ethanol of 1.03 %, sucrose of 4.0 g/100 g, reducing sugar of 3.18 % and total soluble solid content of 8.0°Brix with commercial vinegar (ACV and DV). Descriptive statistical test indicates that there were no significant differences in color intensity, sourness, sweetness, flavor, and aroma with the vinegars tested but OPPB was 56 % more preferred than ACV and DV by the respondents.